Antitrust Law and Economics Review. (McLean, Virginia Antitrust Law and Economics Review, 1967)
The Review provides the proper forum for activities on industrial organization theory; economic analysis of specific antitrust problems (e.g., mergers, price discrimination, exclusive dealing, sales below cost, etc.), and studies of structure, conduct and performance in particular industries.
Quarterly